White Coats: A Possible Source of Nosocomial Infections - Hamid, Maliha; Nawaz, Benish; Afshan, Naheed (PSM Biological Research, 2016)
It has been shown that white coats wore by Medical staff which thought to bring authority and distinction to the medical profession becoming a source of nosocomial transmission of pathogenic microorganisms. In this study we evaluate the different kinds of microorganisms and their intensity present on the white coats of doctors and paramedical staff. In this study we used 100 more than 15 days unwashed white coats which were used and hanged in hospital environment and 100 washed within 15 days and not placed in hospital. The aim of this study was to assess the risk of transmission of pathogenic microorganisms by wearing coats of Doctors and paramedical staff in a hospital environment as well as a comparison of microbial load also being studied between unwashed & home laundered white coats. In this Cross sectional analysis samples were taken through moist swabs from two different areas of the white coat (Pocket and Sleeves) wearing by doctors and lab staffs in different hospital in Karachi, Pakistan. Sample processed in the Microbiology department at Jinnah University for Women according to standard procedures. It was observed that unwashed sleeves and pockets of coats were highly contaminated areas. Bacteria were isolated from the collected samples. In gram positive bacteria 70% Staphylococcus aureus and 30% Staphylococcus coagulase negative bacteria were isolated. In gram negative bacteria 35% Klebsiella, 10% E.coli, 10% Enterobacter, 10% Shigella and 5% Salmonella were isolated while 30% show no growth.